1982
DOI: 10.1177/096032718200100409
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticide Residues in Human Milk in Great Britain, 1979-80

Abstract: 1 The concentrations of some organochlorine pesticides and polychlorobiphenyl compounds have been determined in 102 samples of human milk collected between January 1979 and September 1980. 2 Comparison of the results with those from a limited study undertaken in 1963-4 shows a decline in residues' levels. 3 The concentrations of organochlorine pesticides and polychlorobiphenyls in human milk samples from residents in Great Britain compare favourably with data obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
1999
1999

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…1 The study reported here is the fourth in a series of surveys similarly designed and conducted by the Working Party on Pesticide Residues (WPPR) which has looked at the concentrations of organochlorine pesticide residues found in human milk samples collected throughout the UK. The ®rst study was conducted in 1963 ± 4, 2 the others in 1979 ± 80 3 and 1989 ± 91. 4 An additional small scale survey was also carried out in 1984.…”
Section: Introductionmentioning
confidence: 99%
“…1 The study reported here is the fourth in a series of surveys similarly designed and conducted by the Working Party on Pesticide Residues (WPPR) which has looked at the concentrations of organochlorine pesticide residues found in human milk samples collected throughout the UK. The ®rst study was conducted in 1963 ± 4, 2 the others in 1979 ± 80 3 and 1989 ± 91. 4 An additional small scale survey was also carried out in 1984.…”
Section: Introductionmentioning
confidence: 99%
“…Recalcitrant compounds therefore are found accumulated in mammals, especially in fat tissue, animal milk supplies (Frank and Braun 1989), and also in human milk (Collins et al 1982;Ip and Phillips 1989;Skaare and Polder 1990). Highly sophisticated analytical techniques have been developed for the detection of organochlorines at the trace and ultratrace level (Burse et al 1990).…”
Section: Ring-fission and Subsequent Pathwaysmentioning
confidence: 99%